Graphical interface development for the position control of a 3RRR planar parallel manipulator - Burbano Castillo, Luis Carlos; Trullo Daza, Roger Peregrino; Daraviña Peña, Giancarlo; Quintero Riaza, Héctor Fabio (Scientia et Technica, 2018)
This paper presents the development of a graphical interface implemented in a 3-RRR planar parallel manipulator. The graphical interface allows the control, in open loop, of the position of the manipulator, allowing to locate in the plane the end actuator and define its pose. The graphical interface allows the visualization of variables such as angular position, torque, voltage of the servomotors that drive the input links. The theoretical and real comparison of the angular displacement and the torque in the motors during the chosen path is shown, obtaining very close results between both.